Case study investigation of the revenue implications of the minibus-taxi industry running unscheduled feeder services on a hybrid public transport system in Tshwane - Ngwira, Vera Duduzile (Department of Civil Engineering, 2022)
In South Africa, the minibus-taxi industry (MBI) transports most of the population and contributes notably to the country's socio-economic growth. The industry not only provides accessible and convenient transport, particularly for the most disadvantaged communities, but also creates job and business opportunities. However, due to its informal nature, which is also characterised by unsafe driving, violent taxi wars, poor vehicle conditions, and poor working conditions, among others, formalising the MBI has been the government's goal. The White Paper on National Transport Policy of 1996 states 'the minibus-taxi industry (MBI) will have to be formalised and measures introduced to enhance its economic viability'. The government's efforts to formalise the minibus-taxi industry by implementing the Taxi Recapitalisation Programme (TRP) and Integrated Rapid Public Transport Networks (IRPTNs) have not been as successful as envisaged. Almost 15 years since the TRP implementation in 2005, its objectives to formalise and regulate the industry's business model, labour conditions, and vehicle conditions have not come to fruition. Moreover, the IRPTNs' focus, from 2007, on replacing minibus-taxi services with Bus Rapid Transport (BRT) systems have 'proven to be costly and too difficult to achieve' (Behrens et al., 2017). If anything, the unsuccessful results of these programs have highlighted the need for the government to find ways of collaborating with the MBI as an informal industry and then gradually transforming it. Hence, some cities are considering implementing hybrid public transport systems, whereby the formal (scheduled services) and the informal (unscheduled services) public transport, i.e. BRT and minibus-taxi, coexist in an integrated manner. Consequently, some studies are being conducted on the compatibility of the formal and informal to achieve a feasible overall public transport transformation in South Africa. This research investigated the revenue implication of implementing a trunk (served by formal services) and feeder (served by informal services) hybrid public transport system arrangement on the MBI. The research focused on the impact public transport hybrid systems have on the minibus-taxi drivers whose income is usually the remaining income of farebox revenue after deducting operational costs and vehicle rental and assessing the contributing factors to the impact.The research uses the Hammanskraal to Rainbow Junction to Tshwane CBD trunk and feeder corridor as a case study. The study presents the minibus-taxi operations on the route from Hammanskraal to Rainbow Junction to Tshwane CBD before the implementation of the hybrid public transport system; the City of Tshwane transition process for compensating removed public transport operators on a transport corridor; and hybrid public transport system operations on the same route, after implementation of the hybrid public transport system. The findings demonstrate that the minibus-taxi industry was operating at a loss on the feeder route compared to the pre-hybrid public transport system time. However, only the minibus-taxi drivers took the brunt as the minibus-taxi owners continue to demand the same vehicle rental amount as before. The research shows the need to improve labour conditions in the MBI and the necessity for organised labour for MBI employees (especially minibus-taxi drivers) to represent their interests to their employers and government agencies. Results stemming from the analysis of the factors influencing the MBI revenue loss were that the success of the hybrid public transport systems relies on government agencies to establish a meaningful relationship with the MBI guided by appropriate strategies of incremental transformation. The Hammanskraal to Rainbow Junction to Tshwane CBD Feeder and Trunk corridor was not operating when this study was conducted as minibus drivers refused to support the system.